Perlindungan Hukum terhadap Korban Malapraktik Medis di Masa Pandemi COVID-19: Sebuah Studi Peraturan Perundang-Undangan - Hasbuddin Khalid (SIGn Jurnal Hukum, 2023)
This study examines the forms of legal protection available for victims of medical malpractice. This study uses normative legal research with a statute approach. The collected legal material is then qualitatively analyzed to describe the problem and answer the study objectives. The results show that the complexity of health service provision during the COVID-19 pandemic increases the risk of errors and medical malpractice. The Government has established a series of legal protections, including civil, criminal, and administrative, to facilitate victims of medical malpractice claim their rights. Civil legal protection ensures patients’ rights to seek compensation through out-of-court dispute resolution, such as negotiation, mediation, and arbitration. Meanwhile, criminal legal protection regulated punishments such as imprisonment or a fine for doctors proven guilty of medical malpractice. On the other hand, administrative legal protection provides a complaint mechanism for patients, ensuring that the Government and Honorary Council will impose administrative sanctions on doctors proven guilty of medical malpractice. Therefore, it is recommended that the Government continue strengthening and enhancing public awareness regarding patients’ rights and the available legal protection mechanisms, especially during the COVID-19 pandemic. This role is crucial for empowering the community to protect themselves from potential medical malpractice. Furthermore, healthcare personnel should be given maximum support through adequate facilities and equipment provision, as well as capacity enhancement through ongoing training and education, to enable them to provide optimal health services in the face of this pandemic challenge. In addition, there needs to be a strengthening of the monitoring system and legislation to prevent and effectively handle medical malpractice cases.